Persepsi Etis Penghindaran Pajak: Tinjauan Pengaruh Perilaku Keputusan Investasi dan Love of Money - Abdillah, M. Riduan; Putriana, Astia; Hadiani, Yasir (Shafin: Sharia Finance and Accounting Journal, 2024)
This research aims to find empirical evidence regarding testing the effect of investment decision behavior and love of money on ethical perceptions of tax avoidance in order to answer the challenges of the phenomenon of investment and entrepreneurial education amidst advances in technology and information, especially for the millennial generation who are predominantly from universities. This research focuses on examining financial attitudes/behavior. The rise of investment risk is directly proportional to ethical or non-ethical tax behavior. This research method is a quantitative method. The population of this study were students of the Accounting/Economics Study Program at Universities in South Kalimantan. The sampling technique in this study used a purposive sampling method, obtaining 272 respondents. The research results show that investment decision behavior has no effect on ethical perceptions of tax avoidance. Apart from that, love of money effects the ethical perception of tax avoidance. These empirical findings can be a reference in identifying challenges in order to minimize tax avoidance.